Fiscal Sustainability, Fiscal Reactions, Pitfalls and Determinants - António Afonso; José Carlos Coelho (Center for Economic Studies and ifo Institute (CESifo), 2022)
We examine the sustainability of public finances and its determinants for 19 Eurozone countries from 1995 to 2020. We conclude for the existence of panel cointegration between government revenues and expenditures; primary government balance and one-period lagged public debt-to-GDP ratio; and public debt-to-GDP ratio and one-period lagged primary government balance. The estimated fiscal reaction functions suggest the existence of a Ricardian fiscal regime. Finally, modelling via time-varying coefficients, we find that fiscal sustainability increases with growth, fiscal balances and fiscal rules indices, and decreases with trade openness, current account balances, government effectiveness index, after 2010, and with sovereign ratings assigned by the main rating agencies.
Keywords: C23; H61; H63; E62; 330; fiscal sustainability; budget balance; public debt; panel data; time-varying coefficients; Eurozone; sovereign ratings